Overweight and Obesity in Children under 5 Years: Surveillance Opportunities and Challenges for the WHO European Region - Jones, Rebecca E.; Jewell, Jo; Saksena, Rhea; Ramos Salas, Ximena; Breda, João (Frontiers in Public Health, 2017)
Background Many children who have overweight or obesity before puberty can develop obesity in early adulthood, which is associated with increased morbidity and mortality. The preschool years (ages 0–5) represents a point of opportunity for children to be active, develop healthy eating habits, and maintain healthy growth. Surveillance of childhood overweight and obesity in this age group can help inform future policies and interventions. Objective To review and report available prevalence data in WHO European Region Member States and determine how many countries can accurately report on rates of overweight and obesity in children under 5 years. Methods We conducted a rapid review of studies reporting on overweight and obesity prevalence in children ages 0–5 in the WHO European region member states from 1998 to 2015. Results Currently, 35 of the 53 member states have data providing prevalence rates for overweight and obesity for children under 5 years. There was little consistency in study methods, impacting comparability across countries. The prevalence of overweight and obesity in children under 5 years ranges from 1 to 28.6% across member states. Conclusion Although measuring overweight and obesity in this age group may be challenging, there is an opportunity to leverage existing surveillance resources in the WHO European Region.